Pengaruh Kompleksitas Tugas, Tekanan Waktu, dan Sifat Kepribadian pada Kinerja - Rustiarini, Ni Wayan (UI Scholars Hub, 2013)
The aim of the research in to investigate the influence of task complexity, time pressure, and five traits of auditor personality such as openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism on auditor performance. There have been a number of research findings on task complexity and time pressure on auditor performance, yet none shows consistency. This study, therefore, tries to provide a new point of view by using traits personality of auditor, which are rarely used in the research field of accounting. Participants in this studies are auditors who work on a public account firms in Bali. The results showed that task complexity and time pressure do not have significant effects on auditor performance. Moreover, only three of the five personality variables—conscientiousness, extraversion, and neuroticism—have significant effects on auditor performance.